Analisis de la aplicacion de las NIF y su importancia en el sector pùblico: caso distrito de Santa Marta, periodo 2016-2020 (2021)
The FRS belonging particularly to the public sector for the purposes of this study, every time they are accepted in the world as there are already many more countries that have adopted them, and the main driving forces of their expansion are the stock markets. expansion has had difficulties and Colombia is a clear example as it is a country that even today in many of its companies observes traditional accounting regulations. Economic globalization creates the need to apply international standards and therefore as part of the harmonization process whatever path is preferred such as adoption, adaptation and others, if any. The fundamental reason for this process to collapse is that it is essential for the market to be able to handle financial information that complies with characteristics of comparability, transparency and reliability. This is why applying international financial reporting standards for the public sector is necessary for countries that want to participate in globalization and continue to be or be competitive and be immersed in this same world of globalization.